Extended Spectrum Betalactamase Detection in Enterobacteriaceae Family Strains - Armindo José Perozo Mena; Maribel Josefina Castellano González (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
The high incidence of infectious diseases and the rise of antibiotic-resistant enterobacteria represent a great medical problem today, and the Extended Spectrum Betalactamase (ESBL)-producing strains are an example of this phenomenon. In order to determine the production of ESBL in strains pertaining to the Enterobacteria family, isolated in the Bacteriological Reference Center at Maracaibo's University Hospital from January 2006-December 2007, 3883 strains of enterobacteria were analyzed, distributed among 14 different species. To detect ESBL, the Kirby-Baüer test was used as a preliminary method, following the CLSI guidelines; additionally, confirmatory tests such as double disc synergy, the combined disc and E-test ESBL methods were used. Of all the enterobacteria studied, 951 (24.49%) were ESBL producers. K. oxytoca (43.33%), K. pneumoniae (40.10%), and Enterobacter cloacae (31.54%) were the microorganisms with greater ESBL production. When correlating ESBL production with the patient services, a statistically significant association (p0.05) between ESBL production and the ICU was detected. These results reflect that excessive antibiotic use produces the appearance and dissemination of resistance.